1989
DOI: 10.1177/0887302x8900700309
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dress on Students' Perceptions of Teacher Characteristics

Abstract: The purpose of this study was to examine the influence of a female teacher's clothing style on student perceptions of teacher characteristics, including approachability, knowledge, respect, and overall acceptability. High school students were provided with photographs of a teacher model dressed in four clothing styles and were asked to select one of the photos for each of 20 statements designed to reflect teacher characteristics. Chi square results revealed differences between the clothing styles on 19 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…a good deal of attention in recent years as women have increasingly sought to obtain executive and managerial positions. Whereas the influence of clothing on first impressions has been widely studied (Butler & Roesel, 1989;Conner, Peter, & Nagasawa, 1975;Douty, 1963;Lennon & Miller, 1984-85;Rosencranz, 1962), the impact of clothing on decisions to hire women has received little systematic attention in the literature. One exception is the Cox study (1984,1985) which found that increased masculinity of women's clothing resulted in more positive perceptions of management characteristics and more favorable hiring recommendations among industrial personnel administrators.…”
Section: Sandra M Forsythementioning
confidence: 99%
“…a good deal of attention in recent years as women have increasingly sought to obtain executive and managerial positions. Whereas the influence of clothing on first impressions has been widely studied (Butler & Roesel, 1989;Conner, Peter, & Nagasawa, 1975;Douty, 1963;Lennon & Miller, 1984-85;Rosencranz, 1962), the impact of clothing on decisions to hire women has received little systematic attention in the literature. One exception is the Cox study (1984,1985) which found that increased masculinity of women's clothing resulted in more positive perceptions of management characteristics and more favorable hiring recommendations among industrial personnel administrators.…”
Section: Sandra M Forsythementioning
confidence: 99%
“…Informal clothing is not always negative, though, because instructors dressed in informal clothing style (jeans and a sweater) were rated as most approachable and flexible, yet elicited ratings of least respect [25]. According to Butler and Roesel [25], teachers in jeans are viewed as fun, approachable, not especially knowledgeable, commanding limited respect, not looking like a teacher, but generally the style students prefer overall. In contrast, the suited teacher was seen as unapproachable, not especially fun, but someone who possessed the image of a teacher.…”
Section: Instructor Clothing As Communicationmentioning
confidence: 99%
“…Teaching assistants wearing formal clothing received a higher score on credibility, intelligence, and preparation than those wearing semiformal or informal clothing [24]. Informal clothing is not always negative, though, because instructors dressed in informal clothing style (jeans and a sweater) were rated as most approachable and flexible, yet elicited ratings of least respect [25]. According to Butler and Roesel [25], teachers in jeans are viewed as fun, approachable, not especially knowledgeable, commanding limited respect, not looking like a teacher, but generally the style students prefer overall.…”
Section: Instructor Clothing As Communicationmentioning
confidence: 99%
“…A majority of studies have found that the more formal business attire a teacher wears, the more positive responses they receive in respect and power, but conversely they also receive the least positive response for approachability (Davis, Clarke, Frances, et al 1992;Morris, Gorham, Cohen, & Huffman, 1996;Lukavsky, Butler, & Harden, 1995;Butler, & Roesel, 1989). This creates an issue because educators want to portray power and authority in their classrooms, but not to the point where students feel they cannot approach teachers with questions or issues they may be facing.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Within the limited research that has been done in teacher attire, most has focused on student initial perceptions of teacher character traits, or first impressions, by using doctored photographs and other such methods (Davis, Clarke, Frances, et al 1992;Morris, Gorham, Cohen, & Huffman, 1996;Lukavsky, Butler, & Harden, 1995;Butler, & Roesel, 1989). A majority of studies have found that the more formal business attire a teacher wears, the more positive responses they receive in respect and power, but conversely they also receive the least positive response for approachability (Davis, Clarke, Frances, et al 1992;Morris, Gorham, Cohen, & Huffman, 1996;Lukavsky, Butler, & Harden, 1995;Butler, & Roesel, 1989).…”
Section: Review Of Related Literaturementioning
confidence: 99%